Pathology induced by Newcastle disease virus AF2240 strain in Japanese quails (Coturnix coturnix japonica) - Idris, Lokman Hakim; Abdul Razak, Intan Shameha; Ahmad, Hafandi; Mohd. Noor, Mohd. Hezmee; HN, Atikah; BN, Farhana (Onderstepoort Veterinary Institute, 2015)
Atikah HN, Hezmee MNM, Hafandi A, Intan-Shameha AR, Farhana BN, Lokman HI, Pathology induced by Newcastle disease virus AF2240 strain in Japanese quails (Coturnix coturnix japonica). Onl J Vet Res., 19(8): 497-507, 2015. Quails could become potential carriers of Newcastle disease (ND). We report susceptibility/pathology in Japanese quails (Coturnic corturnix japonica) to ND virus AF2240, a viscero-tropic velogenic strain isolated during an outbreak in Malaysia in the 60’s. Three groups of six 2 week old quails each, were injected antigen 0.1ml, 0.2ml or 0.3ml EID50 7.3log10/0.1ml intramuscularly with a non-injected control group. Six days after infection all dosed quails presented ruffled feathers, depression, incoordination, lameness, anorexia, diarrhoea, recumbency and paralysis of wings and legs. There were no increases in antibody titers in any group (ELISA). All groups except controls, showed variable congestion and haemorrhage of intestine, congestion of liver, brain, pectoral muscles, heart and lungs. The findings suggest that quails are susceptible to NDV AF2240 virus but that there was no dose dependent viral effect.